Psychometric properties of the Psychological Problem Change Expectancy Scale - Žuljević, Dragan; Rakočević, Nikolija; Gavrilov Jerković, Vesna (Psihološka istraživanja, 2019)
The Psychological Problem Change Expectancy Scale (PPCES)is an instrument designed to assess the client’s outcome expectations of a psychological treatment. It is based on theAnxiety Change Expectancy Scale (ACES; Dozois & Westra, 2005). The expectancies regarding the psychological change as a treatment outcome expectation are conceptualized as a system of client’s prognostic beliefs about the consequences of participation in some kind of psychological treatment, i.e. the client’s expectation of improvement of his/herstate as a consequence of participation in a psychological treatment. This paper was aimed atevaluating the basic metric characteristics of the ACES adaptation. The adaptationconsisted of translating the items into Serbian language and changing the content in order to generally imply to the psychological problem which had been the reason for a person to seek a professional help. The research incorporated two separate studies. In Study 1, conducted on the sample of 171 clients beginning the psychological treatment, the internal consistency and the latent structure of the scale were investigated by exploratory factor analysis (EFA). In Study 2, conducted on the sample of 240 students participating in ananalogue study, the construct validity was additionally checked by confirmatory factor analysis (CFA). The results of the EFA suggested a high heterogeneity of the scale, while the CFA, due to the impossibility of confirming the original model, suggested a potential shortening of the scale from the initial twenty to eleven items, organized into the bifactor model. The items were organized in two specific factors – change optimism and change pessimism, together with the general factor – treatment outcome expectations. Concurrent validity was confirmed by adequate correlations with the measures of dispositional optimism, self-efficacy and the measures of subjective well-being. It can be concluded that the PPCES scale is a reliable and valid instrument for assessing the expectations of treatment outcomes, but it is more structurally homogeneous in the form of 11 items compared to the initial structure. Because of the specificity of the samples from both studies, future research should additionaly check the structural validity of the PPCES, especially within the clinical population and more homogeneous psychotherapy samples.